Conservative treatment of intra-articular calcaneal fracture: a retrospective analysis - Lucena, Igor Freitas de; Costa, Marco Túlio (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate patients who received conservative treatment for a displaced intra-articular calcaneal fracture and to correlate the clinical-functional outcomes with the calcaneus shape measured using radiographs at the last outpatient visit. Methods: A retrospective study was performed with patients who suffered calcaneal bone fractures and were treated nonsurgically between 2006 and 2016. Radiographic (Böhler’s and Gissane’s angles, calcaneal width, talar declination angle, and calcaneal pitch) and clinical-functional parameters (American Orthopedic Foot and Ankle Society (AOFAS) and visual analog scale (VAS) pain scores and personal satisfaction) were evaluated. Results: We found no relationship between the measured angles and the clinical-functional outcomes. Conclusion: Despite the small number of cases evaluated in this study, the clinical-functional ankle and hindfoot AOFAS scale score was considered satisfactory in most cases. We found no relationship between the calcaneus shape measured using radiographic parameters and the clinical-functional outcome. Level of Evidence IV; Therapeutic Studies; Case Series